Effects of Sugar in Adult Diet on the Development and Reproduction of Spodoptera frugiperda (J. E. Smith) under Laboratory Conditions in Burkina Faso - SALO, Pousbila; SALOU, Wendemanegde Ernest; GUIRE, Rasmané; ZONGO, Eliasse; KAM, Sami Éric; OUEDRAOGO, Georges Anicet; KOAMA, Kouliga Benjamin; MEDA, Nâg-Tiéro Roland (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), is the pest causing enormous economic losses to Maize production. To date, there is little documentation on rearing protocols for S. frugiperda. This study aimed to evaluate the effect of honey and glucose as a nutrient source on the developmental parameters and reproduction of S. frugiperda under laboratory conditions. In this work, we compared the larval period, larval survival, pupal period, pupal survival, adult longevity, female oviposition period, female fecundity and egg hatching of S. frugiperda adults under three feed diets: distilled water (D1), 10% bee honey with water solution (D2) and 10% glucose with water (D3). The longest larval period and highest larval survival were achieved on D3. The longest longevity, oviposition and post-oviposition periods, the highest fecundity and number of eggs per female per day were observed on D3. The diet D3 had significant effects on live cycle of S. frugiperda parameters compared with D1 and D2. Our results will enable us to improve mass rearing of S. frugiperda in laboratory.